Ответы и объяснения

  • njhieyjdf
  • почетный грамотей
2014-02-22T18:12:58+04:00
А)7(х-1)=3х     б)9(х+7)=-х     в)5(х-3)=4х      г) 4(х+6)=х        д)-х=4(6+х)
7х-8=зх            9х+63=-х         5х-15=4х         4х+24=х            -х=24+4х
7х-3х=8            9х+х=-63         5х-4х=15        4х-х=-24             -х-4х=24
5х=8                10х=-63             х=15             3х=-24                -5х=24
х=1.6               х=-6,3                                     х=-8                   х=-4.8